2022
DOI: 10.1371/journal.pone.0277486
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome sequences of eight Orostachys species: Comparative analysis and assessment of phylogenetic relationships

Abstract: We analyzed the complete chloroplast genomes of eight Orostachys species and compared the sequences to those of published chloroplast genomes of the congeneric and closely related genera, Meterostachys and Hylotelephium. The total chloroplast genome length of thirteen species, including the eight species analyzed in this study and the five species analyzed in previous studies, ranged from 149,860 (M. sikokianus) to 151,707 bp (H. verticillatum). The overall GC contents of the genomes were almost identical (37.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…nivea , where the rps19 gene was present at the boundary between the LSC and Irb. The fate of genes located at the boundaries of each region also depends on the extension or contraction of specific regions of the plastome, which can be used for the phylogenetic classification of taxa [ 49 , 50 , 51 , 52 ]. For example, in the genus Camellia (Theaceae), variations in the length of the IR regions due to various indels in the plastome have been observed [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…nivea , where the rps19 gene was present at the boundary between the LSC and Irb. The fate of genes located at the boundaries of each region also depends on the extension or contraction of specific regions of the plastome, which can be used for the phylogenetic classification of taxa [ 49 , 50 , 51 , 52 ]. For example, in the genus Camellia (Theaceae), variations in the length of the IR regions due to various indels in the plastome have been observed [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies utilizing cp. genomes have successfully yielded high-resolution and well-supported phylogenetic trees, even in phylogenetically challenging plant taxa [ 15 , 16 , 31 , 33 ]. In our study, we constructed a phylogenetic tree based on the alignment of chloroplast whole-genome sequences from Q. disciformis , Q. dinghuensis , Q. blakei , and Q. hui , along with 17 other closely related species of section Cyclobalanopsis .…”
Section: Discussionmentioning
confidence: 99%
“…Hylotelephium is known to be a very difficult group to classify due to the high external morphological variation of each taxon and the very similar morphological characteristics between species [ 15 , 24 ]. According to these findings, many morphological and molecular phylogenetic studies have been conducted, but the delimitation of this genus and phylogenetic relationships between its species remain insufficiently resolved [ 16 23 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, various molecular phylogenetic studies [ 16 23 ] have been performed and revealed a large phylogenetic distance between the two genera; Hylotelephium formed a clade with Sinocrassula A. Berger, Orostachys , and Meterostachys Nakai ( Telephium clade), and Sedum was in the Acre clade. However, in most studies, including studies using ITS of nuclear DNA [ 16 , 18 ] and some marker regions of the chloroplast genome [ 19 ], as well as whole chloroplast genome sequences [ 23 ], the taxonomic position of Hylotelephium as an independent genus was not supported because it formed a paraphyletic clade with Orostachys species. Therefore, studies are needed to evaluate an accurate taxonomic position by identifying the exact phylogenetic relationship between two genera.…”
Section: Introductionmentioning
confidence: 99%